Variability of Exserohilum turcicum (Leo. and Sug.): an incitant of Northern Corn Leaf Blight of maize and its management with Bacterial endophytes - Malakar, Pranab; Devi, R. K. Tombisana (Umiam : CPGS-AS, CAU, 2024)
Maize (Zea mays L.) holds significant importance as the world's third leading cereal crop, following rice and wheat. It is susceptible to various pathogens that significantly impact its yield. Northern corn leaf blight (NCLB), also known as turcicum leaf blight, caused by Exserohilum turcicum (Leo. and Sug.), is a prominent foliar disease affecting corn worldwide. It is very important to manage disease initially and management with bacterial endophytes had proven to be effective in many crops. Percent disease index (PDI) was highest (52.6) in Lumshnong (East Jaintia Hills) in 2019 whereas highest (51.6) in Chokpot (South Garo hills) in 2021.District wise, West Garo hills (49.58) had highest PDI in 2019 followed by South Garo hills and Ri-Bhoi whereas PDI was highest in South Garo hills (49.29) in 2021.Isolate RBEt 02 (134X 18.1) has larger conidia size, followed by SGEt 01 and EJEt 03 whereas WGEt 02 has the smallest conidia size (41.5 X 11.1).WJEt 01 had more growth at pH 5 compared to the other isolates. RBEt 02 had more growth at pH 7 and 9 compared to the other isolates. SGEt 01 and SGEt04 had more growth at pH 9 than at pH 7. EKEt 01 and WKEt 01 had less growth at all the pH levels. RBEt 02 was found to be most virulent (9.753) among the other isolates. EKEt 02was least virulent (2.744). MGEB026 had recorded with highest percent inhibition (61.18%) followed by MGEB132 and MGEB140.Only 18 isolates were selected further for in vitro antimicrobial and plant growth promotion assay based on their dual culture assay. Maize treated with MGEB026 (2814.8) bacteria had more vigour followed by MGEB057. Least vigour was observed with MGEB148 isolate. MGEB026, MGEB106, MGEB132, MGEB057 and MGEB208 were compatible with each other and used for further study.MGEB132 was found to be more tolerant to Aluminium at different concentrations followed by MGEB106. MGEB026 is least tolerant to Aluminium. MGEB106 was found to be more tolerant to Acid at different pH followed by MGEB132. MGEB208 is least tolerant to Acidic condition.MGEB208, MGEB132, MGEB057, MGEB106 and MGEB026 are identified as Orchobactrum sp., Bacillus cereus, Staphyllococcus pasteurii, Burkholderia sp. and Achromobacter piechaudii respectively. Combination of MGEB208, MGEB132, MGEB057, MGEB106 and MGEB026 (Microbial consortia) showed better performance in terms of disease suppression, growth attributes such as plant height, no. of leaves and yield attributes.MGEB106 showed better performance among the screened isolates in terms of disease suppression, growth attributes such as plant height, no. of leaves and yield attributes. Management of NCLB in Meghalaya condition , these endophytes can be utilised for development of consortia and biopesticides.
Includes bibliographical references and index.
Keywords: Exserohilum turcicum -- Management; Bacterial endophytes